Catalytic material for confinement reinforced singlet oxygen water treatment, preparation method and application

By using the limited domain structure of MnO2 nanotubes and alumina ceramic sphere composite particles in a fixed bed catalytic reactor to activate persulfate to generate singlet oxygen, the problem of low utilization rate and interference in traditional catalysts is solved, and the complexity is achieved Efficient removal of organic pollutants in water quality.

CN119114070APending Publication Date: 2024-12-13NANKAI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411247175.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-06
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

In large-scale industrial applications, traditional fixed-bed catalytic reactors have problems with low catalyst utilization and low mass transfer efficiency, and persulfate is disturbed by natural organic matter and inorganic salts in actual wastewater treatment, which limits its application effect.

Method used

The domain-limited structure is prepared by hydrothermal method by using MnO2 nanotubes and alumina ceramic sphere composite particles, and the domain-limited environment is constructed to activate persulfate to generate singlet oxygen, which is used to remove pollutants in complex water bodies.

Benefits of technology

It realizes efficient removal of organic pollutants, especially phenol, in complex water quality, and is not disturbed by natural organic matter and inorganic ions, improving the selectivity and anti-interference ability of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119114070A_ABST
    Figure CN119114070A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of organic pollutant degradation, and discloses a catalytic material for confinement enhanced singlet oxygen water treatment, a preparation method and application. The MnO2 nanotube and aluminum oxide nano ceramic ball composite particles are prepared, the confinement environment in the MnO2 nanotube on the surface of the ceramic ball can efficiently activate persulfate to directionally generate singlet oxygen, and the singlet oxygen is used for degrading organic pollutants in a complex water body. As a novel water treatment functional material, the MnO2 nanotube and alumina ceramic ball composite particle can be widely applied to a Fenton-like fixed bed or fluid bed filler, shows an excellent degradation effect on organic matters in a complex water body, and has very strong anti-interference capability. The method is short in preparation process flow, simple to operate, high in production efficiency, low in energy consumption, low in equipment requirement and easy to realize industrial production. The method is applied to the field of water treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of organic pollutant degradation, and more specifically, relates to the preparation and application of a catalytic material for confined enhanced singlet oxygen water treatment, which utilizes the confined environment of MnO2 nanotubes on the surface of particles to activate persulfate to directionally produce singlet oxygen to degrade organic pollutants in water. Background Art

[0002] Compared with traditional Fenton-like treatment technologies, although fixed-bed catalytic reactors can immobilize catalysts and are easy to operate, the low dose of catalysts and their low utilization rate affect the overall efficiency of the catalytic reaction. In addition, its membrane structure also limits the contact between the liquid to be treated and the catalyst, resulting in a longer mass transfer process and lower mass transfer efficiency. Therefore, fixed-bed catalytic reactors have certain difficulties in large-scale industrial applications. Fenton-like fluidized bed systems can effectively solve the problem of low catalyst utilization in traditional Fenton-like processes by promoting the contact between the catalyst and the reaction liquid. The carrier particles in the fluidized bed are in a highly dynamic state of continuous flow, migration, and tumbling, which promotes the flow of the reaction liquid between the carrier particles, greatly increases the effective specific surface area of ​​the catalyst, and enables the catalytic reaction to proceed efficiently.

[0003] In the Fenton-like reaction based on persulfate, the OO bond of persulfate is broken after activation, generating reactive free radicals - hydroxyl radical (·OH) and sulfate radical (SO4 ·- ). This type of free radical has a high redox potential and can efficiently oxidize and remove organic pollutants in water. However, the large amount of natural organic matter and inorganic salts coexisting in actual wastewater usually interfere with the utilization of free radicals, thus limiting their application in actual wastewater treatment. Zhang et al. found in "Membrane-Confined Iron Oxychloride Nanocatalysts for Highly Efficient Heterogeneous Fenton Water Treatment" that ·The extremely short lifetime of OH in the aqueous phase (<10μs) limits its mass transfer from the generation site to the water body, which severely limits the effectiveness of free radicals. In addition, natural organic matter coexisting in surface water can block catalytic sites and quench free radicals, making AOP treatment of organic micropollutants ineffective. In contrast, during the persulfate activation process, singlet oxygen produced in the non-radical oxidation pathway has strong anti-interference ability against inorganic anions and complex natural organic matter. For example, in the article "New Insights into Selective Singlet Oxygen Production via the Typical Electroactivation of Oxygen for Water Decontamination", Zhao's team described the efficient production of singlet oxygen by building a redox interface based on copper atomic sites on the electrode, even in the presence of natural organic matter and Na + Mg 2+ The degradation of bisphenol A is almost unaffected by the interference of plasma. However, in the reported catalytic systems for the directional generation of singlet oxygen, the synthesis of most catalysts is relatively complex and requires additional energy. In view of this, in view of the challenges faced by current wastewater treatment, the development of a simple and easy-to-obtain catalyst that promotes the efficient activation of persulfate by the singlet oxygen-dominated pathway is of great significance for actual wastewater treatment. Summary of the invention

[0004] In view of the above problems, the purpose of the present invention is to provide a catalytic material for confined enhanced singlet oxygen water treatment. The prepared MnO2 nanotubes and alumina ceramic ball catalyst particles can be loaded in a Fenton-like bed reaction layer, and singlet oxygen is produced by directionally activating persulfate by constructing a confined environment, and can be used to effectively remove the pollutant phenol in complex water bodies.

[0005] The technical solution of the present invention:

[0006] A catalytic material for confined enhanced singlet oxygen water treatment, the catalytic material comprising MnO2 nanotubes and alumina ceramic balls, the catalytic persulfate activity being controlled by controlling the mass proportion of the MnO2 nanotubes, the content of the MnO2 nanotubes in the catalytic material being 5wt% to 15wt%, and the content of the alumina ceramic balls being 95wt% to 85wt%.

[0007] The diameter of the alumina ceramic balls in the catalytic material is 2-3 mm.

[0008] The diameter of the MnO2 nanotubes in the catalytic material is 4-6 nm.

[0009] A method for preparing a catalytic material for confined enhanced singlet oxygen water treatment comprises the following steps:

[0010] (1) mixing potassium permanganate and concentrated hydrochloric acid uniformly to obtain an initial solution;

[0011] (2) adding alumina ceramic balls into the initial solution and mixing them uniformly by mechanical strong stirring to obtain a reaction system;

[0012] (3) placing the reaction system in a high-pressure reactor to carry out a hydrothermal reaction;

[0013] (4) After the hydrothermal product obtained in step (3) is naturally cooled to room temperature, the solid and liquid are separated; the product is washed and dried to constant weight to obtain a composite particle catalyst of MnO2 nanotubes and alumina ceramic balls, which is a catalytic material.

[0014] In step (1), the concentration of potassium permanganate is controlled to be 0.053 mM, and the concentration of concentrated hydrochloric acid is controlled to be 0.2 mM.

[0015] In step (2), the concentration of alumina ceramic balls in the reaction system is 5.5 g / L-15 g / L.

[0016] In step (3), the hydrothermal reaction temperature is 140° C. and the reaction time is 15 h.

[0017] The application of the above catalytic material in the oxidation and degradation of organic pollutants in water bodies is as follows:

[0018] A reactor containing wastewater to be treated is placed on a mechanical stirring table, and MnO2 nanotube and alumina ceramic ball composite particle catalyst and persulfate are added to the wastewater to be treated. The control conditions are: normal pressure, reaction temperature of 20-30°C, and initial pH of the wastewater of 3-11; the amount of MnO2 nanotube and alumina ceramic ball composite particle catalyst added to the reaction system is 1g / L-5g / L, the concentration of persulfate in the reaction system is 0.3mmol / L-0.5mmol / L, and the reaction is carried out at a rotation speed of 400rpm-500rpm for 5min-40min to oxidize and degrade organic pollutants in the water.

[0019] The organic pollutant is phenol, and its concentration in the reaction system is 0.05 mmol / L.

[0020] The persulfate is potassium peroxymonosulfate (PMS).

[0021] Working principle of the invention: The invention provides a method for confined enhanced singlet oxygen activation of persulfate to generate pure 1The composite catalytic material of O2 includes a carrier and MnO2 nanotubes loaded on the carrier; the carrier is an alumina ceramic ball; the mass of the MnO2 nanotube is 5-15% of the mass of the single-atom catalyst. In the present invention, the alumina ceramic ball is used as the carrier, wherein the MnO2 nanotube provides a confined reaction space of 4-6nm. Different from the outer surface of MnO2, due to the lattice curling of the inner wall of the nanotube, the Mn site on the inner wall of the nanotube has a greater binding energy with the O at the end of the peroxide bond in the persulfate. After the O at the end is anchored by the Mn site, the OO bond breaks at the head end to form an *OH intermediate. The active oxygen O converted from the two oxygen-containing intermediates (*OH) combines to generate a singlet oxygen molecule. This unique adsorption and binding process of persulfate in the confined space results in the persulfate being converted only into 1 O2. 1 O2 is a highly selective oxidant that reacts with unsaturated organic matter through electrophilic addition and electron abstraction reactions to destroy its complete organic structure. 1 O2 has good selectivity and anti-interference ability, so that the confined catalytic system provided by the present invention has excellent selectivity and anti-interference when degrading organic pollutants.

[0022] Beneficial effects of the invention: The invention provides a method for confined enhanced singlet oxygen activation of persulfate to generate pure 1 O2 composite catalytic material. The confined MnO2 nanotube material only needs to simply adjust the hydrothermal synthesis conditions, the preparation process is simple, and the yield is high. At the same time, the confined material only converts into persulfate when activating 1 O2, the confined space can shield the natural organic matter in the water environment so that the activation site is not shielded and can maintain 1 The efficient production of O2 and the 1 O2 is not quenched by inorganic ions in the water body and can still operate effectively in complex water quality, which is of great significance for the treatment of actual wastewater. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The scanning electron microscope image and the transmission electron microscope image of the composite particles NTC-15% of MnO2 nanotubes and alumina ceramic balls prepared in Example 1 of the present invention; wherein a is the scanning electron microscope image of NTC-15%; b is the transmission electron microscope image of NTC-15%;

[0024] Figure 2 are X-ray diffraction patterns of NRC, NTC-15%, NTC-10%, and NTC-5% prepared in Examples 1, 2, and 3 of the present invention and Comparative Example 2;

[0025] Figure 3It is a degradation effect diagram of phenol degradation by NRC, NTC-15%, NTC-10%, and NTC-5% activated persulfate prepared in Examples 1, 2, and 3 of the present invention and Comparative Example 2;

[0026] Figure 4 1 is a graph showing the results of electron paramagnetic resonance and electrochemical tests of Examples 1, 2, 3 and Comparative Example 2 of the present invention; wherein, a is an electron paramagnetic resonance test graph of NRC, NTC-15%, NTC-10%, NTC-5% and PMS prepared in Examples 1, 2, 3 and Comparative Example 2 of the present invention; b is an open circuit potential curve of NRC and NTC-15% electrodes prepared in Example 1 and Comparative Example 2 of the present invention and phenol and PNS;

[0027] Figure 5 It is a degradation effect diagram of phenol degradation by activating persulfate in simulated wastewater with NRC, NTC-15%, NTC-10%, and NTC-5% prepared in Examples 1, 2, and 3 of the present invention and Comparative Example 2;

[0028] Figure 6 These are scanning electron microscope and transmission electron microscope images of NRC and NTC-15% prepared in Example 1 and Comparative Example 2 of the present invention after reacting in simulated wastewater; wherein, a and b are scanning electron microscope images of NRC and NTC-15% after reacting in simulated wastewater, respectively. DETAILED DESCRIPTION

[0029] The specific implementation of the present invention is further described below in conjunction with the accompanying drawings and technical solutions.

[0030] Example 1

[0031] A method for preparing confined structure MnO2 nanotube and alumina ceramic ball composite particles by a hydrothermal method comprises the following steps:

[0032] (1) Mix 0.053 mM potassium permanganate and 0.20 mM concentrated hydrochloric acid to obtain an initial solution.

[0033] (2) 5.5 g / L of alumina ceramic balls are added to the initial solution, and the mixture is mixed evenly by mechanical strong stirring to obtain a reaction system.

[0034] (3) The reaction system was placed in a high pressure reactor and reacted at 140° C. for 15 h.

[0035] (4) After the hydrothermal product obtained in step (3) is naturally cooled to room temperature, it is washed and dried to constant weight to obtain a catalytic material in which MnO2 nanotubes account for 15%; wherein the diameter of the nanotubes is 5 nm, recorded as NTC5-15%.

[0036] Furthermore, a reactor containing wastewater to be treated is placed on a stirring table, and the MnO2 nanotube and alumina ceramic ball composite material prepared in step 4 and persulfate are added into the wastewater, and the control conditions are: normal pressure, reaction temperature of 20-30°C, and initial pH of the wastewater of 3-11; the amount of the MnO2 nanotube and alumina ceramic ball composite material prepared in step 4 added into the reaction system is 1g / L-5g / L, the concentration of persulfate in the reaction system is 0.3mM-0.5mM, and the reaction is carried out at a rotation speed of 400rpm-500rpm for 5min-40min to oxidize and degrade organic pollutants in the water.

[0037] Example 2

[0038] The difference between this embodiment and the specific embodiment 1 is that in step (2), the concentration of alumina ceramic balls is controlled to be 10 g / L, and the catalytic material with a MnO2 nanotube ratio of 10% is recorded as NTC-10%. The rest is the same as the specific embodiment 1.

[0039] Example 3

[0040] The present embodiment is different from the specific embodiment 1 in that the concentration of alumina ceramic balls is controlled to be 15 g / L in step (2), and a catalytic material containing 5% of MnO2 nanotubes is obtained, which is recorded as NTC-5%. The rest is the same as the specific embodiment 1.

[0041] Comparative Example 1

[0042] A method for preparing non-confined structure MnO2 nanorods and alumina ceramic ball composite particles by a hydrothermal method comprises the following steps:

[0043] The present embodiment is different from the specific embodiment 1 in that the concentration of concentrated hydrochloric acid in step (1) is controlled to be 0.15 mM, which is recorded as NRC-p. The rest is the same as the specific embodiment 1.

[0044] Comparative Example 2

[0045] The difference between this embodiment and the specific comparative example 1 is that the reaction temperature and time in step (3) are controlled to be 16 hours, which is recorded as NRC. The rest is the same as the specific comparative example 1.

[0046] The present invention is verified by the following tests:

[0047] Experiment 1: This experiment is the application of MnO2 nanotubes and alumina ceramic ball composite particles in the removal of phenol in water containing natural organic matter, and compares the removal effects of confined materials with different proportions of MnO2 nanotubes and non-confined MnO2 nanorods on phenol. 0.5 mL of 100 mM PMS mother solution prepared with deionized water was added to 100 mL of phenol solution prepared with deionized water, so that the phenol concentration and PMS concentration in the solution were 0.05 mM and 0.5 mM, respectively, and the mixture was fully mixed in a mechanical stirrer at 400 rpm. After adding 200 mg of NRC, NTC-15%, NTC-10% and NTC-5%, the timing was started, and sampling was performed at different sampling times (0, 5, 10, 15, 20, 25, 30, 35 min). After passing through a 0.22 μm PES polyethersulfone membrane, 1 mL of the filtered sample was placed in a centrifuge tube, and 0.5 mL of 10 mmol / L sodium thiosulfate was added to quench the sample. The sample was stored at low temperature (4° C.); the phenol concentration at different sampling times was determined by high performance liquid chromatography, and the removal rate of phenol degradation by activated PMS was as follows: Figure 3 shown.

[0048] Experiment 2: This experiment is to detect the active substances produced when NTC-15% composite particles activate persulfate to remove phenol. Take 0.5mL of 100Mm PMS mother solution prepared with deionized water and add it to 100mL phenol solution prepared with deionized water, so that the phenol concentration and PMS concentration in the solution are 0.05mM and 0.5mM respectively, and mix them thoroughly in a mechanical stirrer at 400rpm. Then add 200mg of MnO2 nanotubes and alumina ceramic ball composite particles NTC-15%, start timing, take samples at a sampling time of 5 minutes, and then pass through a 0.22μm PES polyethersulfone membrane. Take 1mL of the filtered sample and place it in a centrifuge tube. 2,2,6,6-tetramethyl-4-piperidinol (TEMP, >99%) is dissolved in a phosphate buffer solution (pH=7.4) with a final concentration of 50mM. Then, the TEMP solution (40μL) is mixed with the extracted 40μL filtered sample. The mixed solution of TEMP is absorbed by a quartz capillary and the signal corresponding to singlet oxygen is detected from the spin-trapped adduct in EPR. The signal of singlet oxygen in EPR is as follows: Figure 4 As shown in a.

[0049] Experiment 3: 4 mg of material was scraped from the surface of NRC and NTC-15% and ultrasonically dispersed in a mixed solution containing 50 μL naphthol, 30 μL ethanol and 420 μL deionized water. 8 μL of the suspension was transferred to the glassy carbon electrode with a pipette and dried naturally. The electrochemical workstation (CHI 760E, Shanghai Chenhua) was used to measure the open circuit potential. The glassy carbon electrode (GCE) loaded with the prepared nanofibers was used as the working electrode, and the Pt electrode and Ag / AgCl electrode were used as the counter electrode and reference electrode, respectively. 0.1 M Na2SO4 was used as the electrolyte. After the open circuit potential timing started, PMS was added at 500 seconds, phenol was added at 1500 seconds, and after the 2000 second timing ended, the complete open circuit potential curve was obtained as shown in the figure. Figure 4 b. The concentrations of PMS and phenol were the same as those in Experiment 1.

[0050] Experiment 4: This experiment is to test the application of NTC-15% composite particles in activating persulfate to remove phenol in high-salinity wastewater. The difference between this experiment and experiment 1 is that the wastewater to be treated is a 0.05mM phenol solution, which is also mixed with 200mg / L natural organic matter, 5mg / L Cl - 、36mg / L NO3 - , 25mg / LCO3 2- and 10mg / LCa 2+ , 18mg / L Mg 2+ The other parameters are the same as those in Experiment 1. The removal rates of phenol degradation by PMS activated by various MnO2 nanotubes and alumina ceramic ball composites are shown in Figure 2. Figure 5 shown.

[0051] Figure 1 a is a microscopic scanning electron microscope image of the composite particles of MnO2 nanotubes and alumina ceramic balls prepared in Example 1. It can be seen from the image that the MnO2 nanotubes are uniformly dispersed on the ceramic balls, and the MnO2 nanotubes and ceramic balls are successfully composited by a hydrothermal method. Figure 1 b Transmission electron microscopy clearly captures the nanotube morphology of MnO2 and can intuitively prove that the diameter of the nanotube is 4-6nm.

[0052] Figure 4 The X-ray diffraction patterns of the MnO2 and alumina ceramic ball composite particles prepared in Examples 1, 2, 3 and Comparative Example 2 are compared with the α-MnO2 standard spectrum card (PDF standard card: 44-0141). It can be seen that adjusting the hydrothermal conditions only changes the morphology of MnO2, and the MnO2 in the synthesized nanocomposite particles are all α-MnO2.

[0053] Figure 3The degradation effect diagram of phenol degradation by activating PMS with composite particles of MnO2 nanotubes and alumina ceramic balls prepared in Examples 1, 2, 3 of the present invention and Comparative Example 2. It can be seen from the figure that the ability of NRC to activate PMS to remove phenol is limited, while NTR can effectively activate PMS to remove phenol in aqueous solution. When the proportion of MnO2 nanotubes in NTC increases from 5% to 15%, its ability to remove phenol is significantly improved, which proves that the catalytic activity can be controlled by adjusting the loading amount of MnO2 nanotubes.

[0054] Figure 4 a is the electron paramagnetic resonance test graph of the catalyst and PMS prepared in Examples 1, 2, 3 and Comparative Example 2 of the present invention. The confined nanotubes of NTR provide a unique binding mode for PMS. The peroxide bonds of PMS in the nanotubes are broken, and the two ortho-bound PMS molecules are directionally converted into singlet oxygen. With the decrease of the MnO2 nanotube loading in NTC-15%-NTC-5%, the triple signal peak of singlet oxygen also decreases step by step, indicating that the design of the loading amount of MnO2 nanotubes and alumina ceramic balls can regulate the production of singlet oxygen. However, no active substance signal appears in the EPR spectrum of the non-confined material NRC. Figure 4 The open circuit potential curve in b can detect the evolution of the redox state of the catalyst surface in the presence of PMS and organic pollutants. After the addition of PMS, MnO2–(HO)SO3 is formed on the surface of NRC. – The addition of BPA complexes caused the potential of the NRC electrode to rise sharply. When the BPA complex was added, it extracted electrons from phenol and caused self-consumption, which led to a decrease in potential. Since PMS preferentially binds inside NTC-15%, the open circuit potential curve of NTC-15% cannot cause a significant voltage drop. It can be seen that the confined and non-confined reaction spaces change the way the catalyst activates PMS.

[0055] Figure 5 The NRC and NTC series prepared in Examples 1, 2, 3 and Comparative Example 2 of the present invention activated PMS to degrade phenol in simulated industrial wastewater. The water was mixed with 200 mg / L natural organic matter, 5 mg / L Cl - 、36mg / L NO3 - , 25mg / LCO3 2- and 10mg / LCa 2+ , 18mg / L Mg 2+ From the figure, we can see that the singlet oxygen generated in the unique confined space of the NTC series catalyst still maintains a good removal efficiency for the target pollutant phenol. Compared with the non-confined structure NRC, Figure 6As shown in a, organic matter and ionic compounds in the water are coated on the catalyst surface and shield the surface active sites, so the NRC-dependent surface activated PMS is significantly inhibited, resulting in ineffective degradation of phenol. Figure 6 In b, these natural organic matter cannot enter the internal space of NTC-15%, so the activation of PMS is not disturbed. At the same time, the singlet oxygen produced is not affected by inorganic ions, so it still exhibits efficient activation and degradation capabilities even in such an extreme water environment.

Claims

1. A catalytic material for confined enhanced singlet oxygen water treatment, characterized in that: The catalytic material comprises MnO2 nanotubes and alumina ceramic balls. The catalytic activity of persulfate is controlled by controlling the mass proportion of the MnO2 nanotubes. The content of the MnO2 nanotubes in the catalytic material is 5wt%-15wt%, and the content of the alumina ceramic balls is 95wt%-85wt%.

2. The catalytic material according to claim 1, characterized in that The diameter of the alumina ceramic balls in the catalytic material is 2-3 mm.

3. The catalytic material according to claim 1, characterized in that The diameter of the MnO2 nanotubes in the catalytic material is 4-6 nm.

4. A method for preparing a catalytic material for confined enhanced singlet oxygen water treatment, characterized in that: The steps include: (1) mixing potassium permanganate and concentrated hydrochloric acid uniformly to obtain an initial solution; (2) adding alumina ceramic balls into the initial solution and mixing them uniformly by mechanical strong stirring to obtain a reaction system; (3) placing the reaction system in a high-pressure reactor to carry out a hydrothermal reaction; (4) After the hydrothermal product obtained in step (3) is naturally cooled to room temperature, the solid and liquid are separated; the product is washed and dried to constant weight to obtain a composite particle catalyst of MnO2 nanotubes and alumina ceramic balls, which is a catalytic material.

5. The method for preparing a catalytic material for confined enhanced singlet oxygen water treatment according to claim 1, characterized in that: In step (1), the concentration of potassium permanganate is controlled to be 0.053 mM, and the concentration of concentrated hydrochloric acid is controlled to be 0.2 mM.

6. The method for preparing a catalytic material for confined enhanced singlet oxygen water treatment according to claim 1, characterized in that: In step (2), the concentration of alumina ceramic balls in the reaction system is 5.5 g / L-15 g / L.

7. The method for preparing a catalytic material for confined enhanced singlet oxygen water treatment according to claim 1, characterized in that: In step (3), the hydrothermal reaction temperature is 140° C. and the reaction time is 15 h.

8. Use of the catalytic material according to any one of claims 1 to 3 in oxidative degradation of organic pollutants in water, characterized in that: Here are the steps: A reactor containing wastewater to be treated is placed on a mechanical stirring table, and MnO2 nanotube and alumina ceramic ball composite particle catalyst and persulfate are added to the wastewater to be treated. The control conditions are: normal pressure, reaction temperature of 20-30°C, and initial pH of the wastewater of 3-11; the amount of MnO2 nanotube and alumina ceramic ball composite particle catalyst added to the reaction system is 1g / L-5g / L, the concentration of persulfate in the reaction system is 0.3mmol / L-0.5mmol / L, and the reaction is carried out at a rotation speed of 400rpm-500rpm for 5min-40min to oxidize and degrade organic pollutants in the water.

9. The use according to claim 8, characterized in that: The organic pollutant is phenol, and its concentration in the reaction system is 0.05 mmol / L.

10. The use according to claim 8, characterized in that: The persulfate is potassium peroxymonosulfate.